Optimal Portfolios with End-of-Period Target. (26th January 2012) - Shiraishi, Hiroshi; Ogata, Hiroaki; Amano, Tomoyuki; Patilea, Valentin; Veredas, David; Taniguchi, Masanobu
Abstract : We study the estimation of optimal portfolios for a Reserve Fund with an end-of-period target and when the returns of the assets that constitute the Reserve Fund portfolio follow two specifications. In the first one, assets are split into short memory (bonds) and long memory (equity), and the optimality of the portfolio is based on maximizing the Sharpe ratio. In the second, returns follow a conditional heteroskedasticity autoregressive nonlinear model, and we study when the distribution of the innovation vector is heavy-tailed stable. For this specification, we consider appropriate estimation methods, which include bootstrap and empirical likelihood.